Ask a question

What Is The Answer To 4y-3=3y+4 ?

Asking Random Equations !

4 Answers by Expert Tutors

Tutors, sign in to answer this question.
MIGUEL O. | Highly efficient and experienced tutor for Math/PhysicsHighly efficient and experienced tutor f...
4.9 4.9 (9 lesson ratings) (9)

When you have to resolve equations your main objective is to, simply isolate variables from constants, using some algebra properties and operations: distributive; adding, subtracting, multiply or divide constants to both sides of the equation.

In this case, we have a simple first order equation

4y– 3=3y+4

When we look to this equation, we see terms with a variable and a constant and constants on both sides of the equation. So we will have to pass the variable (or terms with variable and constant) to one side and the constants to the other side

Normally you pass the variable to your left side of the equation and constants to the right side .

So in this case we have to bring the term "3y" to the left side and for that we are going to subtract "3y" to both sides of the equation.

Then we got:

4y – 3y – 3 = 3y – 3y + 4
y– 3 = 4

Now we have "– 3" in the left side that we have to pass to the right side of the equation. For that, we have to "add "3" to both sides.

(note : always add if the number or term you want to change side is negative , and subtract if the number or term you want to change side is positive)

In this case our term "– 3" is negative so we have to add "3" in both sides of the equation:

y –3 += 4 +3

A Variable is “x y p q “
A Constant is” numbers”,
A Term is a letter and a number together or only a number or only a letter “4p, 3x, 10q, 55,3 ,100,2 ,p ,q,r,t ,y”

Kelisha S. | Math Tutor for all ages!Math Tutor for all ages!

4y-3 =  3y+4     (Compare like terms)

   +3        +3     (add 3 to both sides in order to isolate the y. 4+3=7)

4y = 3y+7          (now put the y's on one side of the equation)

-3y  -3y              (subtract 3y from each side in order to move it to the other side of the equation)

y=7                    (4y-3y=1y=y)


The object is to isolate the variables and the constants(numbers)

4y -3 = 3y + 4

4y -3 + 3 = 3y + 4 +3 (add 3 to both sides to isolate the y on the left side)

4y = 3y + 7

4y -3y = 3y - 3y = 7 (subtract 3y from both sides to isolate the y on the right)

1y = 7 (1y =y)

Alexander J. | Tutor For All AgesTutor For All Ages
4.6 4.6 (7 lesson ratings) (7)

To add on these answers just remember when you can cancel on side out you need to do the same on the other side. Meaning in your equation:


    +3    +3
4y   =3y+7
-3y    -3y

Akshada L. | Statistics TutorStatistics Tutor

Equestion: 4y-3=3y+4

take y on left side and numbers on other side

4y- 3y= 4+3